2017
DOI: 10.1128/cvi.00370-16
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Toxin Neutralization Assay To Characterize the Serologic Response to Adenylate Cyclase Toxin after Infection with Bordetella pertussis

Abstract: Adenylate cyclase toxin (ACT) is an essential virulence factor of Bordetella pertussis, and antibodies to ACT protect against B. pertussis infection in mice. The toxin is therefore a strong candidate antigen for addition to future acellular pertussis vaccines. In order to characterize the functionality of the immunologic response to ACT after infection, we developed an assay for testing the ability of serum samples from subjects infected with B. pertussis to neutralize ACT-induced cytotoxicity in J774 macropha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…ACT has potent toxic effects against CD-11b/CD-18-expressing phagocytes, such as macrophages or neutrophils (32)(33)(34). To determine the functional capacity of the serum antibodies induced via immunization, we utilized the AC toxin neutralization assay with J774A.1 cells (35). Only sera obtained from mice vaccinated with aP plus ACT or aP plus RTX were able to neutralize the toxicity of ACT in J774A.1 macrophages (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ACT has potent toxic effects against CD-11b/CD-18-expressing phagocytes, such as macrophages or neutrophils (32)(33)(34). To determine the functional capacity of the serum antibodies induced via immunization, we utilized the AC toxin neutralization assay with J774A.1 cells (35). Only sera obtained from mice vaccinated with aP plus ACT or aP plus RTX were able to neutralize the toxicity of ACT in J774A.1 macrophages (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…ACT neutralization assay. ACT is, through a combination of mechanisms, cytotoxic for J774A.1 (ATCC TIB-67) macrophage-like cells, and protection against this effect is the basis for the toxin neutralization assay (35). J774A.1 cells were cultured in Dulbecco's modified Eagle's medium with 25 mM glucose (Gibco).…”
mentioning
confidence: 99%
“…Whole fixed B. pertussis cells contain many more protein antigens than the 3–5 purified pertussis proteins present in various manufacturer’ formulations of DTaP. Some investigators have proposed that additional pertussis antigens are needed [33] such as the B. pertussis virulence factor adenylate cyclase toxin (ACT) which is protective in mice and immunogenic in baboons [34,35 • ]. DTP also contained ligands for several Toll-like receptors, TLR1, 2, 4, 5, 6 and 9 [36] whereas subunit DTaP has only the conventional vaccine adjuvant alum, often faulted for its Th2-bias.…”
Section: Identifying and Fixing The Problem With Dtap Subunit Vaccinesmentioning
confidence: 99%
“…Bp AC-Hly is highly immunogenic. Antibodies are detected in serum of infected non-vaccinated subjects [ 51 , 52 , 53 , 54 ]. Since none of the actual pertussis acellular vaccines contain Bp AC-Hly, it was proposed to use Bp AC-Hly as an antigen for diagnosis.…”
Section: Bordetella Pertussis Adenylate Cyclasementioning
confidence: 99%
“…Recently, Eby et al [ 54 ] demonstrated that anti AC-Hly antibodies developed by humans following infection with B. pertussis consistently neutralize toxin-induced cytotoxicity. They suggest that toxin-neutralization assay can be used to characterize the immunological response to AC-Hly after infection and vaccination [ 54 ].…”
Section: Bordetella Pertussis Adenylate Cyclasementioning
confidence: 99%